Effects of Zofenopril and Thymoquinone in Cyclophosphamide-Induced Urotoxicity and Nephrotoxicity in Rats; The Value of Their Anti-Inflammatory and Antioxidant Properties - Mahmood NN; Rashid BM; Abdulla SK; Marouf BH; Hamaamin KS; Othman HH (Journal of Inflammation Research, 2025)
Neveen Nawzad Mahmood,1 Ban Mousa Rashid,1 Sakar Karem Abdulla,1 Bushra Hassan Marouf,2 Karmand Salih Hamaamin,2 Hemn Hassan Othman1 1Department of Basic Sciences-College of Pharmacy, University of Sulaimani, Sulaimani-Kurdistan Region, Iraq; 2Department of Pharmacology and Toxicology-College of Pharmacy, University of Sulaimani, Sulaimani-Kurdistan Region, IraqCorrespondence: Bushra Hassan Marouf, Department of Pharmacology and Toxicology-College of Pharmacy, University of Sulaimani, Sulaimani-Kurdistan Region, Iraq, Tel +9647701562796, Email bushra.marouf@univsul.edu.iqObjective: The study aimed to investigate whether zofenopril (ZOF), thymoquinone (TQ), or their co-administration effectively ameliorates urotoxicity and nephrotoxicity following cyclophosphamide (CPH) treatment.Methods: A total of 48 Wister Albino female rats were divided into six groups each of eight rats; negative control (NC), positive control (PC), mesna (MS), ZOF, TQ, and ZOF+TQ groups. Normal saline, mesna, ZOF-15mg/kg, TQ-80mg/kg, and their combination were given orally for 19 days to the groups NC, MS, ZOF, TQ, and ZOF+TQ respectively. On the 17th day, a single dose of CPH 200 mg/kg was given intraperitoneally for all the groups except the NC group. Urine was collected over 24 hours before animal scarification for urinalysis. After scarification, blood, and kidney tissue were obtained for assessment of conventional kidney function parameters, novel kidney injury biomarkers, pro-inflammatory cytokines, oxidative status, complete blood count (CBC), and histopathological examination.Results: CPH disturbed the urinary excretion of urea, creatinine, and protein, and significantly elevated novel biomarkers for kidney injury including cystatin-C (Cys-C) (p=0.019) and markedly kidney injury molecule-1 (KIM-1) (p=0.27), the semiquantitative measurement of hematuria revealed significant elevation of hematuria score (p=0.0002), urine pus and protein (p=0.0005). Additionally, CBC-derived inflammatory biomarkers including neutrophil-lymphocyte ratio (NLR) (p=0.001), neutrophil-monocyte ratio (NMR) (p=0.0004), pro-inflammatory cytokine interleukin (IL)-6 (p=0.016) and tumor necrosis factor (TNF)-α (p